Correlation between Vertebral Slippage in Spondylolisthesis with Ligamentum Flavum Thickening in Dr. Soebandi Hospital, Jember, East Java, Indonesia - Heni Fatmawati; Alvin Candra; Nindya Shinta Rumastika; Al Munawir; Muhamad Hasan; I Nyoman Semita (Althea Medical Journal, 2023)
Background: Spondylolisthesis is a vertebral slip condition that compromises the body’s axial alignment and structures such as ligamentum flavum. The ligamentum flavum thickening may play a role in spondylolisthesis. The purpose of this study was to investigate the correlation between the slippage of vertebral body (spondylolisthesis) with ligamentum flavum thickening as a tissue response regarding increased mechanical stress.Methods: An analytical retrospective radiological observational was used a cross-sectional study from the results of MRI examination in Dr. Soebandi Hospital, Jember, Indonesia, collected from 2018-2021 using the simple random sampling method. Ligamentum flavum thickness and the degree of vertebral slip were measured using T2-weighted MR imaging and the correlation was analyzed using Fisher’s exact test. Results: Of 102 spondylolisthesis data records, 34 were taken, being female was the most prevalent cases in the age group above 60 years, with the most vertebral segment shift occurring at the L4–L5 level. There was a significant correlation. (p = 0.02; RR = 4.8) between ligamentum flavum thickening and vertebral slip in spondylolisthesis. Conclusion: The significant correlation between ligamentum flavum thickening and vertebral slip in spondylolisthesis suggest that mechanical stress has caused spondylolisthesis, by inducing chronic inflammation that results in hypertrophy of ligamentum flavum. Lumbar segmental instability due to spondylolisthesis is a factor contributing to the development of ligamentum flavum hypertrophy.